EAF2: a tumor suppressor gene with multi-aspect functions - Ji, Wen-Tong; Cui, Chun-Guo; Wang, Yao (Frontiers in Pharmacology, 2024)
Since ELL-associated factor 2 (EAF2) was identified in 1997 as an androgen response gene, it has been of medical and scientific interest. Early studies demonstrated the tumor-suppressing function of EAF2 in the prostate. Sequencing studies indicated an association between EAF2 and several other malignant diseases and multiple physiological processes, such as transcription, apoptosis, embryogenesis, and DNA repair. Further understanding of EAF2 will provide new opportunities and therapeutic approaches for cancers, especially prostate cancer. This narrative review summarizes the existing knowledge of EAF2 and outlines its potential significance. To our knowledge, this is the first review of the role of this novel tumor suppressor gene and its possible functions.